Pengaruh Kualitas Pelayanan Jasa, Lokasi, Harga Terhadap Kepuasan Pelanggan Jasa Kursus Mengemudi Alif - Pamungkas, Bayu Aji Catur; Wantara, Pribanus (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
The purpose of this study was to determine the effect of service quality, location and price on customer satisfaction with Alif driving course services. This research is a quantitative descriptive research. The research was conducted at the Alif Driving Course. The sample in this study amounted to 96 respondents. Sampling using incidental sampling technique and tested using multiple regression analysis method, F test and t test. Data collection techniques were carried out by questionnaire method. Data analysis using SPSS 22 shows that customer satisfaction with the Alif driving course service can be improved by taking into account the level of service quality, location, and price of the Alif driving course. service quality, location and price have a significant influence on customer satisfaction Alif driving course services.